2020
DOI: 10.7717/peerj.8307
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variation of leaf traits in theTernstroemia lineataspecies complex (Ericales: Penthaphylacaceae) in response to geographic and climatic variation

Abstract: Variation in leaf morphology is correlated with environmental variables, such as precipitation, temperature and soil composition. Several studies have pointed out that individual plasticity can largely explain the foliar phenotypic differences observed in populations due to climatic change and have suggested that the environment plays an important role in the evolution of plant species by selecting for phenotypic variation. Thus, the study of foliar morphology in plant populations can help us identify the envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 56 publications
(72 reference statements)
0
14
0
1
Order By: Relevance
“…Such unexpected results were also confirmed in other woody species: Fagus sylvatica [ 17 ], Castanea sativa [ 60 ] and Ternstroemia lineata DC. [ 72 ]. Meier and Leuschner [ 17 ] noted that beech leaf expansion and stand leaf area along precipitation gradient are, in addition to water availability, controlled by spring temperature and possibly nitrogen supply.…”
Section: Discussionmentioning
confidence: 99%
“…Such unexpected results were also confirmed in other woody species: Fagus sylvatica [ 17 ], Castanea sativa [ 60 ] and Ternstroemia lineata DC. [ 72 ]. Meier and Leuschner [ 17 ] noted that beech leaf expansion and stand leaf area along precipitation gradient are, in addition to water availability, controlled by spring temperature and possibly nitrogen supply.…”
Section: Discussionmentioning
confidence: 99%
“…This study also found some variations in leaf shapes, sizes of petioles, leaves, peduncles, spathes and each zone of spadix. This phenotypic variation within species is the result of the interaction of environmental and genetic factors that was gradually inherited to the offspring (Ramsey et al 1994;Gonzalez et al 2012;Albarrán-Lara et al 2018;Li et al 2018;Alcántara-ayala et al 2020;Ren et al 2020). The leaf size and shape indicated the diversity of leaf morphological phenotypes (Ren et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the value, all specimens were classified as intraspecies. Variations within organisms can be used to study evolution (Alcántara-Ayala et al 2020). The broad distribution of B.longifolia is caused by its wide ecological tolerance and greater chances of long-distance dispersal afforded by its baccate, and therefore presumably animaldispersed.…”
Section: Genetic Variationmentioning
confidence: 99%